The Relationship Between Loneliness and Social Media Addiction in Adolescents - Musdalifah Febriana (Mahogany Journal De Social, 2024)
Recently, the issue of addiction to social media has become topical among adolescents, in particular, the problem of loneliness. This paper concentrates on studying the relationship between loneliness and social media addiction putting into consideration the following demographic (gender, age, and socioeconomic status) and psychological (self-esteem and resilience) factors. It was a cross-sectional survey of validated scales in 400 adolescents. It was demonstrated in the results of Pearson correlation analysis that the loneliness and social media dependency are significantly positively correlated with each other (r = 0.47, p < 0.01). All the data of the multiple regression analysis revealed that loneliness (beta = 0.45, p < 0.001) was certainly the strongest predictor, though females and older adolescents were more dependent. The mediation analysis showed that self-esteem partially mediated this relationship and the moderation analyses showed that resilience moderated the impact of loneliness with the relations to social media dependency. The above results suggest that there is an intervention measure imperative that aims at ensuring resilience and self-esteem to help avert social media dependency among lonely youths.